2021
DOI: 10.21037/acs-2021-cfmcs-34
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary outcomes of continuous-flow biventricular assist devices

Abstract: Background: Significant right ventricular failure (RVF) complicating left ventricular assist device (LVAD) placement has been reported at 10-30%. Although primarily indicated for left ventricular failure, ventricular assist devices (VADs) have become utilized in a biventricular setup to combat right ventricular failure (RVF) following LVAD implantation. With the advent of continuous-flow LVADs (CF-LVADs) superseding their pulsatile predecessors, the shift towards CF-biventricular assist devices (CF-BiVADs) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…In the case of unlikely recovery of RV dysfunction after LV LT-MCS implantation, a biventricular setup of continuousflow VADs has been utilized. This therapeutic approach is complicated by a high rate of pump thrombosis [72]; therefore, implantation of a total artificial heart (THA) remains a valid option. Candidates for TAH are most often considered when HTx candidates suffer from acute irreversible biventricular failure at high risk for imminent death (INTERMACS class 1 or 2) and for whom a suitable donor is not available.…”
Section: Long-term Left-ventricular Mechanical Circulatory Support (Lt-mcs)mentioning
confidence: 99%
“…In the case of unlikely recovery of RV dysfunction after LV LT-MCS implantation, a biventricular setup of continuousflow VADs has been utilized. This therapeutic approach is complicated by a high rate of pump thrombosis [72]; therefore, implantation of a total artificial heart (THA) remains a valid option. Candidates for TAH are most often considered when HTx candidates suffer from acute irreversible biventricular failure at high risk for imminent death (INTERMACS class 1 or 2) and for whom a suitable donor is not available.…”
Section: Long-term Left-ventricular Mechanical Circulatory Support (Lt-mcs)mentioning
confidence: 99%
“…As an alternative, dual HM3 support has been demonstrated, but necessitates either partial cardiotomy (304)(305)(306) or right atrial configuration (307,308). Comprehensive studies are lacking, as reported survival rates with HM3 in an RVAD configuration widely ranges from 30% at 3 months to 92% at 18 months (298,(306)(307)(308).…”
Section: Exit Strategies: Durable Right Ventricular Assist Devicesmentioning
confidence: 99%
“…Most published cases of durable intracorporeal RVAD using bilateral continuous-flow VADs underwent upfront BIVAD and not staged implantation after RVF, which has been associated with worse outcomes ( 297 ). However, patients receiving durable BIVAD support were more acutely ill than those receiving isolated LVAD ( 298 ). When performed simultaneously, durable BIVAD is as effective as total artificial heart regarding survival until transplantation.…”
Section: Early and Acute Right Ventricular Failurementioning
confidence: 99%
“…Some groups have reported biventricular support by HVAD or HM3 in the clinical setting, but there is a lack of in vitro hemodynamic evaluation of the HM3 used as an RVAD for RHF 8–13 . Most notably, in their review of continuous‐flow BVAD outcomes in 2021, Farag et al identified eight studies that used an HVAD for RVAD and three studies that used the HM3 for RVAD 14 . Although the HVAD is not available in the market, comparison with successful CF technologies such as the HVAD and HM3 represent value to study clinical characteristics of CF pumps used as BVAD configurations.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] Most notably, in their review of continuous-flow BVAD outcomes in 2021, Farag et al identified eight studies that used an HVAD for RVAD and three studies that used the HM3 for RVAD. 14 Although the HVAD is not available in the market, comparison with successful CF technologies such as the HVAD and HM3 represent value to study clinical characteristics of CF pumps used as BVAD configurations.…”
Section: Introductionmentioning
confidence: 99%